Project management all-in-one for dummies - Portny, Stanley E. (Stanley Erwin) (--For dummies., 2020)
Project Management All-in-One For Dummies is the premier go-to for PMs looking for hands-on information and advice to take their organizational, planning, and execution skills to new heights.